PROBLEMATIKA PEMBELAJARAN PAI DALAM PEMBENTUKAN KARAKTER ISLAMI PESERTA DIDIK DI SMK SWASTA RAHMAT ISLAMIYAH MEDAN HELVETIA - Siti Julaiha Nasution; Ahmad Darlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problems of Islamic religious education learning in the formation of Islamic character of students at Rahmat Islamiyah Private Vocational School in Medan Helvetia is a very important phenomenon and needs to be considered. The purpose of this study is to describe the problems that arise in learning Islamic religious education to form Islamic character that can be instilled by students at school. The research method used is qualitative descriptive, with data collection techniques of observation, interviews and documentation. While analyzing the data of this research with reduction, data collection and conclusion. The results of this study are: (1) Problems in learning PAI, both the problem of students and the problem of educators at SMK Swasta Rahmat Islamiyah Medan Helvetia. (2) Problems in the formation of Islamic character of students at SMK Swasta Rahmat Islamiyah Medan Helvetia (3) Efforts to overcome problems in PAI learning in the formation of Islamic character of students at SMK Swasta Rahmat Islamiyah Medan Helvetia. To overcome the problems in learning PAI at SMK Swasta Rahmat Islamiyah Medan Helvetia, it is necessary to increase the professionalism of teachers through training, as well as counseling support for students. Strengthening Islamic character can be done through active religious activities and parental involvement. Interactive learning methods should be applied to increase student participation, while Islamic value habituation and teacher exemplarity are key. Regular evaluation and monitoring are needed to ensure the success of learning and character building.